(untitled) (Research, Society and Development, 2022)
The present work aimed to carry out a survey of studies on organizational culture in the public service published between 2012 and 2021 (last 10 years). It is a bibliometric research, based on a quantitative and qualitative approach. Searches were carried out in the databases of events promoted by ANPAD. 60 publications dealing with organizational culture were analyzed, but only 10 publications (16.7%) specifically dealt with OC in the public service. In general, there was homogeneity in publications per year, with no growth or decrease factor being observed in publications involving the theme. Articles of general scope and specific sectors were verified. With regard to authorship, it was found that part of the selected authors (23.8%) had continuity in scientific studies on the subject. As a reflection, it is concluded that there is a need to expand studies on organizational culture in the public service, since studies are still limited, considering the criteria for the potential use of this theme for the implementation of public policies.